ANALYSIS OF INFLUENCING FACTORS ON ONLINE PRODUCT PURCHASING TO COLLEGE STUDENTS OF FEB UBSI JAKARTA - Chusminah SM; Sugiyah (Jurnal Economic Resource, 2020)
This study aimed to determine consumer perceptions in determining online purchase decisions, to produce factors that influence online purchasing decisions, and to show the dominant factors that influence online purchases by students at college. This research, which was conducted in April-June 2020, examined the factors that influence consumer purchasing decisions online for products. The respondents were students of the Business Administration Study Program and Office Administration Study Program, FEB UBSI Jakarta, totaling 1801 respondents. The method used in this research is descriptive analysis and factor analysis using the program of SPSS 24. The results showed that 20 factors were acceptable, and the three factors with the highest value based on the communality test were Returns, Product Availability, and Demography. Refund as the most influencial factor that allows consumers to replace products that are not suitable, or cashback. The available product is the second highest factor, consumers expect to shop online with adequate stock and up-to-date product variants. Demography as the third most dominant factor means that consumers of all ages, genders and varying levels of education have opportunities to shop online.